PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS CTL PADA MATERI POKOK CAHAYA UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA KELAS VIII SMP N 1 KURIPAN - Yunita, Erni; Wahyudi, Wahyudi; Rahayu, Satutik (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2014)
The aims of this research is to develop CTL based instructional instrumenton light conceptand to know the effect of CTL based instructional instrumentâ€™sapplication to increase eighth years student physics achievement. The design is a quasi-experimental research and used R&D method. Research subject was eighth years students at Junior High School 1 Kuripan. Datawere analyzedusingttestatsignificant level5%. The average value ofN-Gain obtainedthrough pretestandposttest data. This indicatesthat theapplication of CTL based instructional instrument on light concept has a positive effecttoincrease eighth student physics achievement.Â So that CTL Based Instructional Instrument can be developedmore widely